Protagonists of a real story: the experience of motherhood in adolescence in the Brazilian countryside (Brazilian Journal of Health Research, 2019)
Teenager: word derived from Latin ‘adolescentia’, which means to grow or grow to maturity. It is a transition phase marked by individual transformations that go beyond biological, psychological and social changes linked to the subject’s sexual development. Objective: The aim of the present study is to understand the challenges of motherhood in the age group 10 - 14 years and the meaning of being a mother based on these girls’ perspective. Methods: Ten participants shared their experiences and spoke about the recent maternal difficulties and wards lived by them in a daily basis. Semi-structured Individual interviews were used in the experiment. Discussions were tape recorded, transcribed and analyzed based on content analysis technique focused on thematic analysis. Results: Results have shown four main axes: the feeling of being a mother, the remarkable change in their lives, the received support and regrets for getting pregnant so young. Conclusion: Based on the results, it is necessary to understand whether there is any problem with being a teenager and to follow up proposals highlighting each social reality experienced by these young women.